Challenges and strategies to encourage women to be entrepreneurs in the industrial revolution era - Gede Sri Darma; Ni Putu Ari Krismajayanti (Review of Management, Accounting, and Business Studies, 2020)
The entrepreneurship sector is one of the business sectors that become a choice for women. In the economic industry of Indonesia, women are actively contributing to small, medium, and large enterprises. The government of Indonesia supports women entrepreneurs to increase the economic welfare of the country. Unfortunately, Indonesia has entered a digital revolution called Industrial Revolution 4.0. One technological advancement today which integrates with the physical, digital and biological world makes fundamental changes to everyday human activities and life. However, this development era is still often hampered due to constraints for women to be entrepreneurs. This research aimed to know if the Educational Factors, Dual Role Factors, and Socio-Cultural Factors be the main challenges for women entrepreneurs. It used the Structural Equation Modelling method and AMOS 26 program. In addition, it obtained strategies to encourage women to be entrepreneurs. Therefore, it showed that the educational factor is not a main constraint and challenge for women entrepreneurs. Women have multiple roles as housewives and women entrepreneurs in the business field. However, this research results obtained that dual role factors are the main constraint for women entrepreneurs, especially in Desa Adat Kuta. Furthermore, improving skills to understand the Internet of Things technology, utilizing digital technology to improve productivity and competitiveness, utilizing e-commerce as a place for creating a business, and participating in entrepreneurship seminars or events supported by the government to face the industrial revolution were the strategies to encourage women to be entrepreneurs in Industrial Revolution 4.0.